EFL Students’ Perception Toward the Use of TED Talks in Speaking Skills - Rachma, Prihatini Nur; Rizal, Daviq (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
Learning to speak is essential, particularly for university students. The use of TED Talks as a teaching tool is suggested as a solution to improve English language skills, particularly speaking, by providing teachers and students with a platform to utilise videos as a valuable teaching resource in the classroom. The data for this study were gathered by a quantitative survey approach. Thus, the purpose of this study is to investigate how students perceive the use of TED Talks to enhance their speaking abilities. The instrument used in this research to collect the data was a questionnaire. The participants were 75 undergraduate English Education students who had watched TED Talks to boost speaking skills. The results show that students' feelings about utilising TED Talks to learn speaking skills have an impact on the way they speak, vocabulary growth, pronunciation, and accent, giving them a boost in confidence, affecting their presentation style, and motivating them to improve their speaking skills. Through this research, it is suggested that TED Talks can be integrated into the learning curriculum to enhance students' speaking skills.